2021
DOI: 10.33003/fjs-2020-0404-341
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Malnutrition Among Children in Rural Farm Households in Ogun State, Nigeria

Abstract: Malnutrition in children is one of the most serious public health problems in Nigeria and also in the world. Therefore, the objective of the study was to measure the prevalence of stunting, wasting and underweight and to assess the socio economic factors that influence the anthropometric indicators among children residing in rural farm households of Ogun State Nigeria.  A cross sectional study was employed and 206 farm households were interviewed using a structured, personally administered questionnaire consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…This nutritional status of the under-5 children members of farm households in the study areas revealed that the percentage of stunted under-5 children is however higher than the national average of 32.0% estimated from the National Nutrition and Health Survey (NNHS) 2018. This result is higher than the report of 23.6% by (Babatunde et al, 2011) in rural Kwara State while it was lower than that of Brhane & Regassa (2014) and Ogunnaike et al, (2020) who found 55.9% and 70% stunting among under-five children in rural Kwara and Ogun States respectively. About 8% of the under-five of cassava farming households were underweight while about 4% were wasted.…”
Section: Determinants Of Under-five Nutritional Status Of Cassava Far...contrasting
confidence: 74%
See 2 more Smart Citations
“…This nutritional status of the under-5 children members of farm households in the study areas revealed that the percentage of stunted under-5 children is however higher than the national average of 32.0% estimated from the National Nutrition and Health Survey (NNHS) 2018. This result is higher than the report of 23.6% by (Babatunde et al, 2011) in rural Kwara State while it was lower than that of Brhane & Regassa (2014) and Ogunnaike et al, (2020) who found 55.9% and 70% stunting among under-five children in rural Kwara and Ogun States respectively. About 8% of the under-five of cassava farming households were underweight while about 4% were wasted.…”
Section: Determinants Of Under-five Nutritional Status Of Cassava Far...contrasting
confidence: 74%
“…The results of the determinants of under-five malnutrition of cassava farming households (Table7) can be compared with previous studies such as that of Smith et al, ( 2005 ) who employed child z-scores as the dependent variable and used ordinary least square (OLS) regression model while Babatunde et al, ( 2011 ) and Ogunnaike et al, ( 2020 ) used the malnutrition category as the regressand and employed Logit regression model. The first section of the table reveals the results of the factors influencing stunting in cassava farm households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropometry is a human body measurement which is commonly used to obtain crucial nutrition details about a sample or population (Babatunde et al , 2011). Previous rural farm household studies have applied anthropometric data to under-five children (Babatunde et al , 2011; Ogunnaike et al , 2020). Empirical studies on anthropometric measurements of adolescent members of households especially rural farm households are scarce.…”
Section: Methodsmentioning
confidence: 99%
“…More so, a study in Northwest Ethiopia also reported 21.8% stunting and 16.9% thinness among school-aged adolescents (Kebede et al, 2021). However, some studies also reported nutrition outcomes and dietary diversity (DD) of both under-five children and women of rural farm households in Nigeria (Lawal and Samuel, 2010;Babatunde et al, 2011;Ukegbu and Ogu, 2017;Ogunnaike et al, 2020;Otekunrin et al, 2022). Likewise, few works have described the relationships that existed between agricultural commercialization and nutritional status of under-five children (Okezie and Nwosu, 2007;Carletto et al, 2017) However, from our knowledge, this study is the first that focuses on the effect of agricultural commercialization on DD and nutrition outcomes of adolescent members of rural farm households.…”
Section: Households In Nigeriamentioning
confidence: 99%